1980
DOI: 10.1530/acta.0.0930396
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-pituitary function in eight anencephalic infants

Abstract: The function of the thyroid pituitary axis was investigated in 8 anencephalic infants with no hypothalamus.Thyrotrophin (TSH), thyroxine (T4), 3,5,3\m='\-triiodothyronine (T3) and 3,3,\m='\5\m='\-triiodothyronine (reverse T3, rT3) were measured in the cord blood in 5 cases and during the first 4 h of life in 3 cases, TSH response to synthetic thyrotrophin-releasing hormone (TRH) (200 \g=m\g iv) was carried out in two cases and thyroid hormone response to bovine TSH (5 IU iv) was evaluated in 3 cases.The fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…By contrast, hypothalamic factors do not appear necessary for thyrotrophic and lactotrophic pituitary cell development [Leroyer-Alizon et al, 1980;Begeot et al, 19841. Other than a few thyroid dysplasias (Table IX), the thyroids of our AN sample were normal. Other studies have found that AN pituitary thyroid-secreting hormone (TSH)-secreting cells and the thyroid gland develop normally in the absence of the hypothalamus and are able to function if adequately stimulated [Grasso et al, 1980;Leroyer-Alizon et al, 1980;Cavallo et al, 198 I]. Interestingly, extrahypothalamic brain thyroid-releasing hormone (TRH) known to be independent of the hypothalamus and synthesized in situ [Jackson and Reichlin, 19771, has been demonstrated in a cell line from the sera cerebrovasculosa of an AN fetus [Ishikawa et al, 19761. One of the principal features of AN is adrenal hypoplasia.…”
Section: Malformations In Other Organ Systemsmentioning
confidence: 99%
“…By contrast, hypothalamic factors do not appear necessary for thyrotrophic and lactotrophic pituitary cell development [Leroyer-Alizon et al, 1980;Begeot et al, 19841. Other than a few thyroid dysplasias (Table IX), the thyroids of our AN sample were normal. Other studies have found that AN pituitary thyroid-secreting hormone (TSH)-secreting cells and the thyroid gland develop normally in the absence of the hypothalamus and are able to function if adequately stimulated [Grasso et al, 1980;Leroyer-Alizon et al, 1980;Cavallo et al, 198 I]. Interestingly, extrahypothalamic brain thyroid-releasing hormone (TRH) known to be independent of the hypothalamus and synthesized in situ [Jackson and Reichlin, 19771, has been demonstrated in a cell line from the sera cerebrovasculosa of an AN fetus [Ishikawa et al, 19761. One of the principal features of AN is adrenal hypoplasia.…”
Section: Malformations In Other Organ Systemsmentioning
confidence: 99%
“…Foetal TSH was positively correlated with foetal fT 4 (r ¼ 0.896, P , 0.001) 27 . Foetal TSH has a higher bioactivity than maternal TSH, and its synthesis is not under hypothalamic control, as shown by the high cord serum TSH concentration found in anencephalic foetuses 28,29 . 31 and are believed to mediate cyclic AMP-independent biological effects of TSH that might be acting as a growth factor for brain development 32 .…”
Section: Introductionmentioning
confidence: 99%
“…There is not a lack of TRH receptors in the pituitaries of the fetal or newborn rats since they have a prompt rise in plasma TSH in re sponse to exogenous TRH [26]. Anencephalic human in fants also appear to have normal pituitary-thyroid func tion, in support of the rat data [27][28][29], TRH is produced in many cells in the body other than the PVN. However, whatever TRH may be in the systemic circulation does not reach the thyrotrophs in sufficient concentration to stimulate TSH secretion, nor does hypothalamic or other central nervous system TRH outside the PVN have any significant effect on TSH secretion [30][31][32],…”
Section: Discussionmentioning
confidence: 96%